2016
DOI: 10.1007/s10652-016-9459-y
|View full text |Cite
|
Sign up to set email alerts
|

Scale dependency of dynamic relative permeability–satuartion curves in relation with fluid viscosity and dynamic capillary pressure effect

Abstract: Capillary pressure-saturation-relative permeability relationships (P c -S w -K r ) are functions of importance in modeling and simulations of the hydrodynamics of two-phase flow in porous media. These relationships are found to be affected by porous medium and fluid properties but the manner in which they are affected is a topic of intense discussion. For example, reported trends in fluid viscosity and boundary conditions effects have been found to be contrary to each other in different studies. In this work, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 67 publications
(111 reference statements)
2
19
1
Order By: Relevance
“…Relative permeability responds to the change of capillary pressure 9,11 and also reflects the stability of the displacement front. The quick decrease in the oil relative permeability demonstrates the more nonuniform front during the displacement process with the viscous oil.…”
Section: Relative Permeabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Relative permeability responds to the change of capillary pressure 9,11 and also reflects the stability of the displacement front. The quick decrease in the oil relative permeability demonstrates the more nonuniform front during the displacement process with the viscous oil.…”
Section: Relative Permeabilitymentioning
confidence: 99%
“…Several equations have been proposed to quantitatively demonstrate the dynamic effect on the P c -S w relationship, [9][10][11] and a widely used equation has been proposed by Hassanizadeh and Gray as follows 12,13 : where P d c represents the dynamic capillary pressure, MPa, dependent on flow dynamics; P s c is the steady capillary pressure at equilibrium conditions, MPa, an intrinsic property of the porous medium-fluid system; S w ∕ t is the time derivative of the wetting fluid phase saturation, s −1 ; τ is the dynamic coefficient, Pa·s; and P w and P nw denote the wetting and nonwetting phase pressure, respectively, MPa.…”
mentioning
confidence: 99%
“…As mentioned above, due to the dynamic effect of the capillary pressure, especially in the case of low permeability rocks, the intrusion pressure (capillary pressure) is related to the flow rate of mercury. Specifically, the faster the flow rate is, the greater is the capillary pressure (Abidoye, ; Goel et al, ). Thus, there is a competitive relationship between the flow rate and capillary pressure at the moment of initial displacement, causing the initial pressure to fluctuate above and below the preset pressure value P c (Abidoye & Das, ; Das et al, ).…”
Section: Sampling and Experimentsmentioning
confidence: 99%
“…The supercritical CO 2 ‐water system has a higher dynamic coefficient than the oil‐water system, and the time required for the system to reach equilibrium increases as the wetted saturation decreases. Additionally, this dynamic coefficient was found to be scale dependent, which can already be predicted by artificial neural network modeling (Abidoye, ; Goel et al, ). Thus, in order to ensure that the CPC can directly characterize the pore structure without being affected by fluid dynamics as mentioned above, the CPC is measured at the lab‐scale under an equilibrium or quasi‐static condition (∂ S Hg /∂ t = 0); namely, in this study, the capillary pressure P c and Hg saturation S Hg are recorded until the set P c reaches the stabilized state.…”
Section: Introductionmentioning
confidence: 99%
“…O'Carroll et al (2005) carried out a series of multistep outflow experiments, and found that the DCP coefficient may be depended on saturation. Goel and O'Carroll (2011) and Goel et al (2016) found that the DCP coefficient was dependent on fluid viscosity. Our previous simulation results also showed a dependency of DCP coefficient on viscosity ratio (Tang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%